The Strategies for Teaching and Learning Qur’anic Reading and Writing in Extracurricular Activities at Madrasahs - Wahyudi, Slamet; Rusdiana, Rusdiana; Semi, Hijar (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
The low level of students' ability to read and write the Qur'an remains an important issue in madrasas, especially at the secondary level. This condition requires appropriate, focused, and sustainable learning strategies, one of which is through strengthening extracurricular activities. This study aims to describe the strategies for teaching Quranic literacy in extracurricular activities at MTs Al-Anshar Tanjung Selor. This study uses a descriptive qualitative approach with primary and secondary data sources. Data collection techniques included interviews, observation, and documentation, while data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the strategies for teaching Quranic reading and writing were implemented through the imla and demonstration methods, which were tailored to the abilities of the students. Supporting factors for learning included readiness to learn, motivation, and student characteristics, while inhibiting factors included time constraints, the learning environment, learning objectives, and the management of extracurricular activities. The findings of this study imply the importance of strengthening planning, effective time management, and the development of contextual learning strategies so that the implementation of the Qur'anic reading and writing extracurricular activity runs more optimally and sustainably.